In vitro Antimicrobial Potency of Lemon Fruit (Citrus limon) Extract on Salmonella typhi - Farhan Haidar Fazlur Rahman; Lindawati Alimsardjono; Sunarni Zakaria (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2020)
Introduction: This study aimed to evaluate minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of lemon fruit (Citrus limon) extract in inhibiting Salmonella typhi growth in vitro.Methods: This research was categorized as a laboratory experimental study. Lemon fruit (Citrus limon) extract was prepared with concentration as follows: 100.000 ppm, 50.000 ppm, 25.000 ppm, 12.500 ppm, 6.250 ppm, 3.125 ppm, 1.562 ppm, 781 ppm, and 390 ppm. Dilution tests with Mueller-Hinton broth medium were performed to determine the MIC. After 24 hours of incubation, isolated Salmonella typhi inside the tube was inoculated back in MacConkey agar plate medium to determine the MBC. Replications were conducted 3 times according to Federer’s formula.Results: MIC of lemon fruit (Citrus limon) extract to Salmonella typhi was determined at 3.125 ppm. Meanwhile, MBC was determined at 6.250 ppm.Conclusion: This study showed the potential antimicrobial effect of lemon fruit (Citrus limon) extract against Salmonella typhi in-vitro. Further studies are still needed to determine its efficacy and safety in vivo and also its full antibacterial spectrum.